PENGARUH JUMLAH SUDU PADA PROTOTYPE PLTMH DENGAN MENGGUNAKAN TURBIN PELTON TERHADAP EFISIENSI YANG DIHASILKAN - Saputra, I Gusti Ngurah; Jasa, Lie; Arta Wijaya, I Wayan (Jurnal SPEKTRUM; Vol 7 No 4 (2020): Jurnal SPEKTRUM, 2020)
Turbine is a component that plays an important role as an energy converter to be able to generate electricity in the Micro Hydro Power Plant (MHP). The turbine used in this prototype is a Pelton tubine. The Pelton turbine is a type of impulse turbine consisting of two blades as a prelude receiver for water jets from the nozzles by utilizing high water heads even though the water discharge is small. This research will discuss the effect of the number of blades on the rotation produced by the Pelton turbine and generator so that it can be seen the voltage, current, power produced that affects the torque value and efficiency obtained on the prototype MHP. This study aims to obtain a turbine runner with the number of blades that can produce the highest efficiency, then a variation of the pelton turbine runner is made with different number of blade parameters from the runner with the number of blades according to the calculation obtained from the reference. Variations in the number of blades used are 14 blades, 16 blades, 18 blades, 20 blades, and 22 blades. The results showed that the addition of the number of blades starting from the smallest caused the performance of MHP to increase, the highest output obtained was using a turbine runner with a number of 22 blades which resulted in a turbine rotation of 852.2 rpm before the generator coupled and 497.2 rpm after coupling the generator. Generator rotation is 2133.8 rpm, Generator Voltage is 15.72 volts, Generator power is 33.7 Watts and Torque is 0.6 Nm. The efficiency value using a runner with a number of blades 22 is 4.54%. The resulting efficiency value is very low because the MHP prototype in                                                                                                          generation is less effective and uses a small generation capacity DC generator, so it cannot generate power as much as hydraulic power.